PENGARUH ROTASI KERJA TERHADAP KOMPETENSI PERAWAT DI KAMAR OPERASI ELEKTIF INSTALASI BEDAH SENTRAL RSUD Dr SAIFUL ANWAR MALANG - Endah Yulia Sasmita; Reny Tri Febriani; Regista Trigandara (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Workassignment brings many positive benefits for the improvement of nurse competence. With job rotation, nurses' motivation and productivity can be maintained. Job rotation also allows the exchange of knowledge between nurses so as to enrich each other's competencies. This study aims to determine the effect of job rotation on the competence of nurses in the Elektif Operating Room of the Central Surgical Installation of RSUD Dr. Saiful Anwar Hospital Malang. Experimental quasy research design with posttest only control design 40 respondents intervention group giving job rotation (20 respondents) and control group without job rotation (20 respondents). Data were collected by questionnaires on employee rotation and nurse competence. Data analysis using independent t test with α = 0.05. The results showed that in the intervention group, almost half of the 12 respondents (30%) had a job rotation in the non-conforming category. In the intervention group, almost half of the 14 respondents (35%) had moderate competence, while in the control group, almost half of the 18 respondents (45%) had low competence. The test results are different from the Independent T Test obtained a value of p = 0.000 which means that there is an influence of job rotation on the competence of nurses in the elective operating room of the central surgical installation of RSUD Dr. Saiful Anwar Malang. Well-designed job rotations can improve nurses' competence from various aspects. By periodically rotating jobs to various units, nurses get the opportunity to hone their skills in various fields.